High‐flow nasal cannulae are associated with increased diaphragm activation compared with nasal continuous positive airway pressure in preterm infants. (13th April 2015) - Nasef, Nehad; El‐Gouhary, Enas; Schurr, Patti; Reilly, Maureen; Beck, Jennifer; Dunn, Michael; Ng, Eugene
Abstract Aim High‐flow nasal cannulae (HFNC) are increasingly used for respiratory management of preterm infants. However, their ability to provide support compared to nasal continuous positive airway pressure (CPAP) has been questioned. We compared the effect of HFNC versus nasal CPAP on diaphragm electrical activity (EAdi) in preterm infants. Methods Preterm infants ≤1500 g were randomised in a crossover design to receive 2 hours of either Infant Flow® CPAP (IF‐CPAP) at 5–6 cmH2O or HFNC with the flow rate adjusted to achieve an equivalent pharyngeal pressure. A feeding catheter with miniaturised sensors was inserted for continuous EAdi measurement. Results The study comprised ten infants. Physiologic parameters and oxygen requirements were not different between the two modes. However, seven infants demonstrated a higher EAdi peak and six showed a higher EAdi tonic on HFNC, even though the mean group data showed no difference between HFNC and IF‐CPAP. Neural inspiratory time was significantly longer with HFNC than IF‐CPAP (0.55 ± 0.11 versus 0.48 ± 0.06 seconds, p = 0.018). Conclusion In this cohort of preterm infants, the majority exhibited greater diaphragm activation, as assessed by neural breathing patterns, when supported with HFNC than IF‐CPAP, suggesting that nasal CPAP may provide more effective respiratory support.